2018
DOI: 10.1111/jopr.12922
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Behavior of Different CAD/CAM Materials for Monolithic, Implant‐Supported Molar Crowns

Abstract: It was possible to conclude that all of the tested CAD/CAM materials can be used as monolithic, implant-supported molar crowns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Additionally, silicone fit checker was used on the intaglio surface to further confirm the internal fit. If the crown was found to be of satisfactory fit, it was selected for cementation on individual dies [ 40 , 41 , 42 , 43 , 44 ]. Thirty-one crowns satisfied the criteria for marginal and internal fit, whereas one Zi crown was newly fabricated, as it did not meet the required criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, silicone fit checker was used on the intaglio surface to further confirm the internal fit. If the crown was found to be of satisfactory fit, it was selected for cementation on individual dies [ 40 , 41 , 42 , 43 , 44 ]. Thirty-one crowns satisfied the criteria for marginal and internal fit, whereas one Zi crown was newly fabricated, as it did not meet the required criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The fracture load value was recorded with the relevant software, and the first drop was marked as corresponding load at failure. The maximum load necessary to fracture each specimen was recorded in Newtons (N) [ 42 , 44 , 58 ]. The mode of failure of crowns was recorded according to a classification method [ 58 , 59 ] as follows: Type I: minimal fracture or crack in the crown.…”
Section: Methodsmentioning
confidence: 99%
“…Other published in vitro studies compared the fracture resistance after thermomechanical loading of various CAD/CAM materials on molars. Investigated cemented ISSC were: feldspathic (VITA Mark II: 1130 ± 220N), resin‐matrix ceramic (Lava Ultimate: 2490 ± 510N), LDS (IPS e.max CAD: 2645 ± 545N) (45 N, 1.2 million cycles); 15 feldspathic (Cerec Blocs: 2147 ± 412N), resin‐matrix ceramic (Lava Ultimate:1755 ± 124N) and LDS (IPS e.max CAD: 2804 ± 303 N) (250 N, 1 million cycles) 17 . For screw‐retained ISSC fracture loads after 1.2 million chewing cycles with 50N at 1.6 Hz and thermal cycling (5‐55°C) of lithium silicate ceramic (Celtra Duo: 2302 ± 798N), resin‐matrix ceramic (Cerasmart: 977 ± 129N), LDS (IPS e.max CAD: 3070 ± 376N) and polymer‐infiltrated ceramic network (Enamic: 1750 ± 277N) were recorded 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies with applied fatigue tests and accelerated aging protocols can predict lifetime estimations and potential sources of failure of all‐ceramic restorations. So far, only a few studies tested cemented LDS ISSC in the molar region under laboratory conditions with fatigue application 15–17 . However, a current trend toward screw‐retention, especially for single‐unit restorations can be observed, as these have fewer biological complications than cemented solutions and allow easier access in case of technical complications 18–21 .…”
mentioning
confidence: 99%
“…Fatigue behaviors are important for the clinical long-term prognosis of prosthodontic restorative materials. The results of several studies have shown that SM-based monolithic LS2 implant-supported single crowns survived after dynamic loading, thermocycling, and aging [121][122][123][124]. The full anatomical e.max CAD crowns prepared in monolithic form provide fatigue resistance by increasing the mechanical stability, which is enabled by the ability of a single-piece structure to withstand higher forces.…”
Section: Lithium Disilicate Glassmentioning
confidence: 99%